The Practice of Euthanasia in Medicine in Review of Maqashid Asy-Syari'ah, Medical Code of Ethics, and Criminal Law in Indonesia - Rahadian Faisal; Saeful Rohman (Ad-dawl : Jurnal Islamic Studies, 2025)
Euthanasia is a medical procedure to end the life of a terminally ill patient. This study aims to examine the medical practice of euthanasia from three main approaches: maqashid asy-syari'ah, medical code of ethics, and Indonesian criminal law, distinguishing between active and passive euthanasia. The research approach used is qualitative with a literature study method, referring to primary and secondary sources such as classical and contemporary Islamic literature, KODEKI, the Criminal Code, and related journals and theses. The results show that from the perspective of maqashid asy-syari'ah, active euthanasia cannot be justified because it contradicts the objectives of sharia in protecting life. Meanwhile, passive euthanasia becomes a space for ijtihad with strict conditions, especially in cases of brain death and futility of treatment. Indonesian medical ethics state that the main duty of doctors is to protect human life, so that active euthanasia violates the principles of beneficence and non-maleficence. Passive euthanasia is not considered an ethical violation, but rather part of end-of-life care. However, it must be done carefully, according to procedure, and documented. In Indonesian criminal law, active euthanasia is categorized as murder, even if it is based on compassion or the patient's request, as stipulated in Article 344 of the Criminal Code. Indonesian criminal law does not explicitly regulate the termination of futile medical treatment. This creates legal uncertainty for doctors. All three approaches agree that active euthanasia is unacceptable, as it contradicts the fundamental principle of protecting life. All three still leave room for discussion in the case of passive euthanasia. The absence of clear regulations increases the potential for conflict between medical, legal, and spiritual values. Therefore, it is necessary to strengthen regulations, ethical education, and contextual understanding of maqashid asy-syari'ah to provide ethical and legal guidance in end-of-life medical decision-making.